Kajian Fungsi Al-Qur’an Dalam Kitab Qalb Al-Qur’an: Pusoko Sapu Jagad Cokrojoyo Karya K.H Nawawi Dan Kyai Hammam Nashiruddin (Analisis Aspek Informatif-Performatif Sam D. Gill) - Sofula Khoirun Nada; Adrika Fithrotul Aini (al-Afkar, Journal For Islamic Studies, 2022)
Study of the Functions of the Qur'an in the Book of Qalb Al-Qur'an: Pusoko Sapu Jagad  Cokrojoyo by K.H Nawawi and Kyai Hammam Nashiruddin (Sam D. Gill's Informative-Performative Aspect Analysis) As an effort to prevent stagnation in religious studies, especially the Qur'an, this paper examines the Qur'an from an external perspective with the hope that many new data will be revealed. This paper examines the function of the Qur'an in the core/heart verses of the Qur'an contained in the book of Qalb Al-Qur'an; Pusoko Sapu Jagad Cokro Joyo by K.H Nawawi and Kyai Hammam Nashirudiin uses the informative and performative function theory promoted by Sam D. Gill. The study process in question aims to increase scientific treasures, reveal cultural transmission and transformation, and obtain alternative cultural developments. This study uses a qualitative research method with a descriptive-analytic approach. The descriptive-analytic approach attempts to interpret the data by analyzing the data in detail and then describing it. This research is research-based literature (Library Research). The primary source of this research is the book of Qalb Al-Qur'an; Pusoko Sweeps the Universe Cokro Joyo himself. The results of this study prove that the core/heart verse in the Qalb Al-Qur'an can be divided into verses with informative function aspects with a total of 93 verses and verses with performative aspects totaling 21 verses. Verses with informative aspects are indicated by the information contained in them, while verses with performative aspects are based on people's treatment of them.